Replication data for 'Effects of particle precipitation on the polar mesospheric summer echoes observed by EISCAT VHF 224 MHz radar' - Narayanan, Viswanathan Lakshmi (DataverseNO, 2021)
The EISCAT VHF 224 MHz radar data measuring the mesospheric heights and D region ionosphere used in the manuscript 'Effects of particle precipitation on the polar mesospheric summer echoes observed by EISCAT VHF 224 MHz radar' submitted for review are provided herein. The data discussed in the work are collected on 15 - 17 July 2019 and 09 - 10 August 2019. The radar spectrum in the frequency range of -333 to +333 Hz are provided. Also the outputs of optimized Gauss fits made to the spectrum are provided.